2021
DOI: 10.1292/jvms.21-0021
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical evaluation of epithelial–mesenchymal transition in epithelial tumors of dogs and cats

Abstract: Epithelial-mesenchymal transition (EMT) plays a crucial role in metastasis of epithelial tumors; however, it is challenging to detect EMT by cytology. In the present study, EMT was visualized by fluorescenceimmunocytochemistry (FICC). Air-dried smears from epithelial tumors of dogs (n = 22) and cats (n = 9) were stained using mouse monoclonal anti-E-cadherin and rabbit monoclonal anti-vimentin antibodies.Enzymatic immunohistochemistry (IHC) revealed that 51.6 % (8/22 in dogs, 8/9 in cats) of the cases showed E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Another possible and interesting approach, and also more feasible in veterinary medicine, was described in a recent study. Furusawa and colleagues elegantly showed how performing immunocytochemistry (IHC) on cytology samples of canine and feline tumors allowed a fast assessment of tumor malignancy based on the IHC expression of EMT markers [ 308 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…Another possible and interesting approach, and also more feasible in veterinary medicine, was described in a recent study. Furusawa and colleagues elegantly showed how performing immunocytochemistry (IHC) on cytology samples of canine and feline tumors allowed a fast assessment of tumor malignancy based on the IHC expression of EMT markers [ 308 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…In human medicine, it has been reported that EMG is associated with the metastatic process in many different types of epithelial malignant tumors such as breast cancer and SCC. In small animal medicine, it has been suggested that EMG occurs during the metastatic process of canine prostate carcinoma and canine mammary carcinoma (Furusawa et al, 2021). On the other hand, other studies have reported that EMG contributes to the aggressiveness of oral SCCs in cats (Harris et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our case was classified as grade II based on tubule formation, nuclear pleomorphism and mitotic count. Because neoplastic cells are very anaplastic, immunohistochemistry was performed with cytokeratin and vimentin (Sawa et al 2017), E-cadherin (Furusawa et al 2021), estrogen and progesterone receptors and Ki-67 antibodies (Dagher et al 2019a). The immunohistochemistry results revealed the cytoplasmic staining of cytokeratin in neoplastic cells (Figure 2b), mild (+) staining for E-cadherin, moderate (++) staining for estrogen and progesterone receptors and about 50 to 70% of staining for Ki-67.…”
mentioning
confidence: 99%